Exploring the prevalence of reasons adolescents feel unwelcome at school - Kristen M. Lucibello; Lin Zheng; Scott T. Leatherdale; Karen A. Patte (PLoS ONE, 2026)
Cultivating positive school climates has been recognized as a global and Canadian priority for adolescent health, academic achievement, and development. Feeling welcome at school is an early contributor to overall positive school climate, although detailed understanding of different reasons adolescents may not feel welcome at school at the population-level is limited. The present study examined the prevalence of reasons students felt unwelcome at school and the characteristics of students endorsing each reason. Self-report survey data were used from students ( N = 15,610, M age ± SD = 15.6 ± 1.2, 48.1% girls) from 41 secondary schools in Ontario, Canada, that participated in the 2022–2023 wave of the COMPASS study. Frequencies calculated the prevalence of each reason for feeling unwelcome at school. Overall, 63.4% of students felt unwelcome at school for at least one reason. Appearance (29.6%), another reason (23.3%), marks at school (19.3%), emotional/psychological challenge (15.7%), and race/ethnicity/culture (10.6%) were the most common reasons for feeling unwelcome at school. Overweight perception, gender diverse identity, and low perceived relative financial affluence were overrepresented in participants that felt unwelcome at school relative to the overall sample. The many reasons adolescents feel unwelcome at school need to be addressed as schools focus on building positive and inclusive school climates, and should be considered across multiple levels (e.g., teacher training, students’ learning materials, policy).